BALANÇO DE RADIAÇÃO NO PERÍMETRO IRRIGADO SÃO GONÇALO - PB MEDIANTE IMAGENS ORBITAIS - BERNARDO BARBOSA DA SILVA; ALEXANDRA CHAVES BRAGA; CÉLIA CAMPOS BRAGA (Revista Caatinga, 2011)
The net radiation is of great importance in studies related to energy and mass exchanges between the land surface and atmosphere, although it is not measured routinely in a meteorological network. In this sense, the use of satellite images over the last decade has been increasingly used for its determination. The present study aimed at determining the radiation balance in the Irrigated São Gonçalo Project - PISG and surrounding areas based on satellite images and a few meteorological data measured within the PISG. Landsat 5 Thematic Mapper images available in 2008 and procedures of SEBAL - Surface Energy Balance Algorithm for Land were used for mapping albedo and net radiation. Three selected areas into the study scene were used to discuss the behavior of different components of the radiation balance under different soil cover types. It was observed that the waters of São Gonçalo dam presented albedo in the range of 3.3 to 7,5%, while in the soil with low vegetation cover the albedo ranged between 32 and 38,7% over the studied period. In the irrigated coconut orchard the albedo ranged between 15.0 to 18.7%, while the net radiation values over the dam and the coconut orchard were consistently higher than those in other areas. It was concluded that the irrigated areas have lower albedo and surface temperature and thus increased net radiation, contributing to reduce the air temperature locally.